Political myths of the populist discourse - Stoica, Mihnea S. (Journal for the study of religions and ideologies, 2017)
Studies point out that populism, a concept still in dire need of clarifications, resembles more of a rhetorical strategy than a fully-fledged ideology. Actually, populism has become a concept so frequently used that its orginial meaning seems to have been lost, leaving it as an empty shell, at least from an ideological point of view. I argue that in spite of this - or rather as a means of compensation - populism uses a very robust mythological apparatus, creating narratives that allow voters to easily understand its messages. The current article underlines that in an attempt to over-simplify its discourse, populism makes use of all four political myths identified by Raoul Girardet. The conspiracy myth represents the main element revolving around the populist discourse. Politicians who embrace this rhetoric denounce a secret society that is rigorously organized, the actions of which defy morality, using all means to attain political power. The other three political myths, i.e. the myth of unity, the myth of the savior and the myth of the golden age, act together only as a counterweight for the first. The paper also points out that the success of Euroscepticism lies in the fact that it represents the perfect embedding for such myths, and that the EU needs to generate its own narratives if it hopes to confront the so-called “populist temptation”.